Rāzī : master of Quranic interpretation and theological reasoning - Jaffer, Tariq (Oxford University Press, 2014)
This study investigates the transformative contributions that Fakhr al-Dīn al-Rāzī made to the Islamic intellectual tradition. It focuses on the ways that Rāzī exploited the rich heritage of ancient and Islamic philosophy to interpret the Qur'ān, and on the ways that he forged a methodology for Sunni orthodoxy by uniting reason with the Qur'ān and prophetic traditions (naql). The book proposes that Rāzī gave his intellectual agenda an indisputed authority in Sunni Islam by using the Qur'ān as a vehicle for his ideas.